Disinfection By-Products in Swimming Pool Water and Possibilities of Limiting Their Impact on Health of Swimmers - Ratajczak, Katarzyna; Piotrowska, Alicja (Geomatics and Environmental Engineering, 2019)
The presence of water disinfection by-products (DBPs) in the pool environment is a threat to the health of the users of swimming pools. Due to the mechanism of DBP formation, we are not able to prevent their presence. However, there are several ways to prevent the harmful effects of DBPs on the health of pool users; among these, various kinds of methods that result in the reduction of combined chlorine and DBPs precursors should be mentioned. And last but not least, a new approach to the design of the ventilation system for indoor swimming pools seems to be crucial for the above-mentioned purpose.